C-Kit expression in smooth muscle cells reduces atherosclerosis burden in hyperlipidemic mice. (May 2021) - Zigmond, Zachary M.; Song, Lei; Martinez, Laisel; Lassance-Soares, Roberta M.; Velazquez, Omaida C.; Vazquez-Padron, Roberto I.
Abstract: Background and aims: Increased receptor tyrosine kinase (RTK) activity has been historically linked to atherosclerosis. Paradoxically, we recently found that global deficiency in c-Kit function increased atherosclerosis in hyperlipidemic mice. This study aimed to investigate if such unusual atheroprotective phenotype depends upon c-Kit's function in smooth muscle cells (SMC). Methods: We studied atherosclerosis in a SMC-specific conditional knockout mice (Kit SMC ) and control littermate. Tamoxifen (TAM) and vehicle treated mice were fed high fat diet for 16 weeks before atherosclerosis assessment in the whole aorta using oil red staining. Smooth muscle cells were traced within the aortic sinus of conditional c-Kit tracing mice (Kit SMC eYFP) and their control littermates (Kit WT eYFP) by immunofluorescent confocal microscopy. We then performed RNA sequencing on primary SMC from c-Kit deficient and control mice, and identified significantly altered genes and pathways as a result of c-Kit deficiency in SMC. Results: Atherosclerosis significantly increased in Kit SMC mice with respect to control groups. In addition, the loss of c-Kit in SMC increased plaque size and necrotic core area in the aortic sinus of hyperlipidemic mice. Smooth muscle cells from Kit SMC eYFP mice were more prone to migrate and express foam cell markers (e.g., Mac2 and MCAM) than those from control littermate animals. RNAseq analysis showed a significant upregulation in genes associated with cell proliferation, migration, lipid metabolism, and inflammation secondary to the loss of Kit function in primary SMCs. Conclusions: Loss of c-Kit increases SMC migration, proliferation, and expression of foam cell markers in atherosclerotic plaques from hyperlipidemic mice. Graphical abstract: Image 1 Highlights: c-Kit, a well-known stem cell marker, plays an important role in smooth muscle cells. c-Kit deficiency increases smooth muscle cell migration to atherosclerotic lesions. c-Kit deficiency increases smooth muscle cell-derived foam-cell formation. c-Kit expression decreases atherosclerosis unlike other receptor tyrosine kinases.